My early work on international monetary problems - MACHLUP, F. (PSL Quarterly Review, 2013)
The article is the first in a series of three in which the author reviews his work in international monetary economics. In this instalment, author’s publications over the period 1923 to 1940 are surveyed. JEL: B31, E40, F33